Odpowiedź:
y + [tex]\frac{3}{6}[/tex] = x + [tex]\frac{1}{3}[/tex] - 1
2x + y = 1
y + [tex]\frac{1}{2}[/tex] = x + [tex]\frac{1}{3}[/tex] - 1
y = 1 - 2x
1 - 2x + [tex]\frac{1}{2}[/tex] = x + [tex]\frac{1}{3}[/tex] - 1
y = 1 - 2x
-2x - x = [tex]\frac{1}{3}[/tex] - 1 - [tex]\frac{1}{2}[/tex] - 1
y = 1 - 2x
-3x = [tex]\frac{1}{3}[/tex] - [tex]\frac{1}{2}[/tex] - 2 |×6
y = 1 - 2x
-18x = 2 - 3 - 12
y = 1 - 2x
-18x = -17
y = 1 - 2x
x = [tex]\frac{17}{18}[/tex]
y = 1 - 2([tex]\frac{17}{18}[/tex]) = 1 - [tex]\frac{34}{18}[/tex] = 1 - 1[tex]\frac{16}{18}[/tex] = -[tex]\frac{16}{18}[/tex] = -[tex]\frac{8}{9}[/tex]
x = [tex]\frac{17}{18}[/tex]
y = -[tex]\frac{8}{9}[/tex]